2020
DOI: 10.21053/ceo.2019.01081
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Change of Cortical Temporal Processing in Cochlear Implant Users

Abstract: Objectives. Cochlear implant (CI) users typically report impaired ability to understand speech in noise. Speech understanding in CI users decreases with noise due to reduced temporal processing ability, and speech perceptual errors involve stop consonants distinguished by voice onset time (VOT). The current study examined the effects of noise on various speech perception tests while at the same time used cortical auditory evoked potentials (CAEPs) to quantify the change of neural processing of speech sounds ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Consistent with previous studies (e.g., Kubo et al, 2001;Beynon et al, 2005;Obuchi et al, 2012;Soshi et al, 2014;Grasel et al, 2018;Han et al, 2020), P300 amplitudes were significantly larger and latencies were significantly shorter for the NH group than for the CI group. For the present bimodal CI listeners, mean P300 amplitude and/or latency values were comparable to those observed in previous studies with CI listeners (e.g., Iwaki et al, 2004;Sasaki et al, 2009;Grasel et al, 2018;Abrahamse et al, 2021;Calderaro et al, 2020;Van Yper et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies (e.g., Kubo et al, 2001;Beynon et al, 2005;Obuchi et al, 2012;Soshi et al, 2014;Grasel et al, 2018;Han et al, 2020), P300 amplitudes were significantly larger and latencies were significantly shorter for the NH group than for the CI group. For the present bimodal CI listeners, mean P300 amplitude and/or latency values were comparable to those observed in previous studies with CI listeners (e.g., Iwaki et al, 2004;Sasaki et al, 2009;Grasel et al, 2018;Abrahamse et al, 2021;Calderaro et al, 2020;Van Yper et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The current findings pertain to the early stages of cortical auditory processing (here, the N1/N1(CI) component) in response to nonspeech stimuli under passive listening conditions, and thus demonstrate a cortical imbalance in fundamental auditory processing of low-level acoustic features, such as frequency and intensity, that are known to be reflected in the early typical N1 component in hearing individuals (Dimitrijevic et al, 2008(Dimitrijevic et al, , 2009. Whilst studying this most basic level of auditory processing, upon which more complex processes are built, can give us an indication of how vulnerable the underlying pathways may be to later processing and perceptual difficulties, it would be important to also examine higher order responses to complex speech stimuli and known neural markers of active speech processing such as the P2 component (Han et al, 2020). Individuals with CIs may be able to work around these lower level vulnerabilities that we identify here by developing strategies such as increasing attention and listening effort, using semantic and situational context, and exploiting information from visual cues to aid successful spoken communication.…”
Section: Unilateral Deprivation Underlies Cortical Imbalance and An O...mentioning
confidence: 99%
“…Among the EEG components, it has been shown that the fidelity of N1/P2 is capable of predicting SiN performance in various populations, such as cochlear implant (CI) users and children with learning disorders ( 17 19 ). For instance, CI users revealed decreased N1 amplitude and delayed P2 latency in response to SiN listening, while the cortical responses are significantly associated with behavioral SiN measures ( 18 ). Neural responses in simulated unilateral CI users are temporally delayed for noise-vocoded speech tasks ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalography (EEG) has been applied to study effects of a masker on speech processing since it is sensitive to subtle neural changes and has excellent temporal resolution. Among the EEG components, it has been shown that the fidelity of N1/P2 is capable of predicting SiN performance in various populations, such as cochlear implant (CI) users and children with learning disorders (17)(18)(19). For instance, CI users revealed decreased N1 amplitude and delayed P2 latency in response to SiN listening, while the cortical responses are significantly associated with behavioral SiN measures (18).…”
Section: Introductionmentioning
confidence: 99%